PLCδ1 Protein Rescues Ischemia-reperfused Heart by the Regulation of Calcium Homeostasis - Lim, Soyeon (Nature Publishing Group, 2014)
Myocardial Ca(2+) overload induced by ischemia/reperfusion (I/R) is a major element of myocardial dysfunction in heart failure. Phospholipase C (PLC) plays important roles in the regulation of the phosphoinositol pathway and Ca(2+) homeostasis in various types of cells. Here, we investigated the protective role of PLCδ1 against myocardial I/R injury through the regulation of Ca(2+) homeostasis. To investigate its role, PLCδ1 was fused to Hph1, a cell-permeable protein transduction domain (PTD), and treated into rat neonatal cardiomyocytes and rat hearts under respective hypoxia-reoxygenation (H/R) and ischemia-reperfusion conditions. Treatment with Hph1-PLCδ1 significantly inhibited intracellular Ca(2+) overload, reactive oxygen species generation, mitochondrial permeability transition pore opening, and mitochondrial membrane potential elevation in H/R neonatal cardiomyocytes, resulting in the inhibition of apoptosis. Intravenous injections of Hph1-PLCδ1 in rats with I/R-injured myocardium caused significant reductions in infarct size and apoptosis and also improved systolic and diastolic cardiac functioning. Furthermore, a small ions profile obtained using time-of-flight secondary ion mass spectrometry showed that treatment with Hph1-PLCδ1 leads to significant recovery of calcium-related ions toward normal levels in I/R-injured myocardium. These results suggest that Hph1-PLCδ1 may manifest as a promising cardioprotective drug due to its inhibition of the mitochondrial apoptotic pathway in cells suffering from I/R injury.